Synaptic vesicle docking: sphingosine regulates syntaxin1 interaction with Munc18. - Paola G Camoletto; Hugo Vara; Laura Morando; Emma Connell; Fabio P Marletto; Maurizio Giustetto; Marco Sassoè-Pognetto; Paul P Van Veldhoven; Maria Dolores Ledesma (PLoS ONE)
Consensus exists that lipids must play key functions in synaptic activity but precise mechanistic information is limited. Acid sphingomyelinase knockout mice (ASMko) are a suitable model to address the role of sphingolipids in synaptic regulation as they recapitulate a mental retardation syndrome, Niemann Pick disease type A (NPA), and their neurons have altered levels of sphingomyelin (SM) and its derivatives. Electrophysiological recordings showed that ASMko hippocampi have increased paired-pulse facilitation and post-tetanic potentiation. Consistently, electron microscopy revealed reduced number of docked vesicles. Biochemical analysis of ASMko synaptic membranes unveiled higher amounts of SM and sphingosine (Se) and enhanced interaction of the docking molecules Munc18 and syntaxin1. In vitro reconstitution assays demonstrated that Se changes syntaxin1 conformation enhancing its interaction with Munc18. Moreover, Se reduces vesicle docking in primary neurons and increases paired-pulse facilitation when added to wt hippocampal slices. These data provide with a novel mechanism for synaptic vesicle control by sphingolipids and could explain cognitive deficits of NPA patients.